Cognitive, affective and behaviors’ attitudes towards learning Arabic as a Second Language: a case study at SMKA Maahad Hamidiah Kajang, Selangor, Malaysia - Mamat , Arifin; Noh, Ahmad Sabri; Wan Mahmud, Wan Hamiah (International Organisation of Scientific Research (IOSR), 2013)
The purpose of this study was to investigate the relationship between the attitude of students studying Arabic language as a second language and their achievement in the Lower Secondary Examination (PMR). The research also investigated which component of attitude; cognitive, affective and behaviour, gives most impact on achievement in PMR examination. The study was conducted in SMKA Maahad Hamidiah Kajang, Selangor, Malaysia. The instrument used was a questionnaire with 34 items. It was distributed to 132 Form Four students.The study employed descriptive and inferential statistics in the data analysis. The study revealed that the cognitive and affective components of attitude were found to be significantly correlated with achievement. However, the result also showed that there was no relation between the behaviour component and achievement. In addition, the cognitive component of attitude was found to contribute significantly to achievement in Arabic. Thus, the finding of this study suggests that attitude is crucial in determining achievement in Arabic language. Therefore, teachers should encourage positive attitude towards learning Arabic among students in order to improve their achievement in the subject.